2009
DOI: 10.1002/bem.20480
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to a MRI‐type high‐strength static magnetic field stimulates megakaryocytic/erythroid hematopoiesis in CD34+ cells from human placental and umbilical cord blood

Abstract: The biological response after exposure to a high-strength static magnetic field (SMF) has recently been widely discussed from the perspective of possible health benefits as well as potential adverse effects. To clarify this issue, CD34+ cells from human placental and umbilical cord blood were exposed under conditions of high-strength SMF in vitro. The high-strength SMF exposure system was comprised of a magnetic field generator with a helium-free superconducting magnet with built-in CO2 incubator. Freshly prep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 28 publications
0
10
0
1
Order By: Relevance
“…Moreover, magnetic-fluid-loaded liposomes were guided to the near vicinity of human adenocarcinoma prostatic cells by means of a 0.29-T external magnet [25]. Except for sporadic reports on the influence of magnetic fields on hematopoietic progenitor cells [26], neural progenitor cells [27] and myoblasts [28] to date no report exists investigating on possible effects of magnetic fields on iron-labeled and unlabeled human stem cells. In this study an innovative labeling protocol for tracking MSCs by MRI using SPIO in combination with magnetic fields was established.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, magnetic-fluid-loaded liposomes were guided to the near vicinity of human adenocarcinoma prostatic cells by means of a 0.29-T external magnet [25]. Except for sporadic reports on the influence of magnetic fields on hematopoietic progenitor cells [26], neural progenitor cells [27] and myoblasts [28] to date no report exists investigating on possible effects of magnetic fields on iron-labeled and unlabeled human stem cells. In this study an innovative labeling protocol for tracking MSCs by MRI using SPIO in combination with magnetic fields was established.…”
Section: Introductionmentioning
confidence: 99%
“…Effects of 1.5 T and 3 T‐exposure protocols were consistently and reproducibly seen in all independent experiments performed (three samples for each GMF protocol used with experiments performed at least in duplicate). Interestingly, a previous study has shown that proliferation and differentiation of human CD34+ from human placental and umbilical cord blood were both affected by exposure to 10 T static magnetic field [Monzen et al, ]. In particular, authors showed that after 16 h exposure there was significant increase of BFU‐E and this effect was accompanied by a significant up‐regulation of cell cycle‐related genes and genes involved in early‐hematopoiesis such as c‐KIT , GATA2 , and RUNX1 .…”
Section: Discussionmentioning
confidence: 99%
“…As such, EMFs have been suggested as promising tools to positively influence different steps of neurogenic and osteogenic processes [Boyette and Herrera‐Soto, ; Bai et al, ; Di Lazzaro et al, ; Ongaro et al, ; Podda et al, ; Leone et al, , ]. On the other hand, epidemiological reports, although controversial, suggest a possible association between exposure to EMF and frequency of childhood leukemia [IARC, ; Calvente et al, ] thus prompting studies evaluating effects of EFs on human hematopoietic stem/progenitor cells [Nafziger et al, ; Reipert et al, ; Monzen et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…The authors showed that 3 T SMF exposure alone neither affected the expression of 498 proteins/genes from human embryonic lung fibroblasts (Hel 299 cells) [Schwenzer et al, ] nor induced double‐stranded breaks in human promyelocytic leukemia cells (HL‐60 cells) or CD34+ human acute myeloid leukemia cells (KG‐1a cells) [Schwenzer et al, ]. However, when cells were exposed to strong SMFs with a field gradient, several studies reported biological effects caused by exposure [Hirose et al, ; Sakurai et al, , 2009; Monzen et al, ]. In particular, Monzen et al [] examined the effects of SMF with a high gradient (41.7 T/m) or a 10 T SMF without a magnetic field gradient for 4 or 16 h on CD34+ cells and showed that the magnetic field gradient played an important role in upregulating megakaryocytic/erythroid hematopoiesis in CD34+ cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, when cells were exposed to strong SMFs with a field gradient, several studies reported biological effects caused by exposure [Hirose et al, ; Sakurai et al, , 2009; Monzen et al, ]. In particular, Monzen et al [] examined the effects of SMF with a high gradient (41.7 T/m) or a 10 T SMF without a magnetic field gradient for 4 or 16 h on CD34+ cells and showed that the magnetic field gradient played an important role in upregulating megakaryocytic/erythroid hematopoiesis in CD34+ cells. Repeated studies using different cell lines (HL‐60 cells [Hirose et al, ], osteoblasts [Sakurai et al, ], and insulin‐secreting cells [Sakurai et al, ]) have been conducted by the same group.…”
Section: Discussionmentioning
confidence: 99%